Crystallization and preliminary X-ray diffraction studies of Xanthomonas campestris PNPase in the presence of c-di-GMP - Wang, Yu-Chuan (2013)
Bacterial polynucleotide phosphorylase (PNPase) is a 3'-5' processive exoribonuclease that participates in mRNA turnover and quality control of rRNA precursors in many bacterial species. It also associates with the RNase E scaffold and other components to form a multi-enzyme RNA degradasome machinery that performs a wider regulatory role in degradation, quality control and maturation of mRNA and noncoding RNA. Several crystal structures of bacterial PNPases, as well as some biological activity studies, have been published. However, how the enzymatic activity of PNPase is regulated is less well understood. Recently, Escherichia coli PNPase was found to be a direct c-di-GMP binding target, raising the possibility that c-di-GMP may participate in the regulation of RNA processing. Here, the successful cloning, purification and crystallization of S1-domain-truncated Xanthomonas campestris PNPase (XcPNPaseΔS1) in the presence of c-di-GMP are reported. The crystals belonged to the monoclinic space group C2, with unit-cell parameters a = 132.76, b = 128.38, c = 133.01 Å, γ = 93.3°, and diffracted to a resolution of 2.00 Å.